Qualidade de vida relacionada à saúde e fatores associados em um município de pequeno porte durante a pandemia de COVID-19 - Pezzin, Josiane (2023)
Quality of Life (QL) is about the individual's perception of their position in life in the context of the culture and value systems in which they live and in relation to their goals, expectations, standards and concerns. For healthcare applications, the term HealthRelated Quality of Life (HRQoL) is often used. Research in this area is of great relevance to aid in the development of public policies, evaluation of outcomes in clinical trials and economic analysis. However, population-based research on HRQoL, conducted in different sociocultural settings, is scarce. In this sense, this work aimed to evaluate HRQoL and its associated factors in a small brazilian municipality during the period of the COVID-19 pandemic. This is an epidemiological, cross-sectional, population-based study carried out through a household survey, during the period from november to december 2021 in the city of Alegre/ES, Brazil. The sample was representative of the city's urban population and consisted of individuals aged ≥ 18 years. Through face-to-face interviews, self-reported sociodemographic data, life habits, health-related characteristics, comorbidities and an assessment of HRQoL were collected using the EQ-5D-3L instrument. Data were submitted to statistical analysis and presented in the form of graphs and tables. The association between HRQoL levels and the explanatory variables collected using the Tobit regression model was tested. The study was approved by the UFES Research Ethics Committee under Opinion nº 3,428,060. 694 individuals were interviewed, predominantly female (72.9%) and mean age was 53 years (SD = 18.9). The most prevalent comorbidities were high blood pressure and anxiety. In the analysis of the EQ-5D, 43.23% of the interviewees reported the absence of problems in all dimensions. The dimension with the highest frequency of problems was pain/discomfort, followed by anxiety/depression. The mean HRQoL value obtained was 0.818 (SD = 0.195) on the EQ-5D descriptive system and 77.8 (SD = 18.9) on the EQ-VAS visual analogue scale. The correlation between these values was positive and moderate. The factors that maintained an association with HRQoL in the final Tobit regression model (p ≤ 0.05) were: self-perceived health, disability, polypharmacy, hospitalization in the last year, anxiety, rheumatoid arthritis, obesity and medication adherence problems. In general, the influence of these factors on HRQoL is already well discussed in the literature, except for problems with medication adherence. Along with polypharmacy, this factor highlights the importance of strengthening pharmaceutical care services and multidisciplinary teams in health care in Alegre/ES. The profile of reporting problems in the dimensions of the EQ-5D3L is consistent with that found in national and international studies. The results of this study present a health assessment of a small municipality, useful for local health managers, and which enriches the literature in the area with data on HRQoL in settings and contexts that have been little studied.